2021
DOI: 10.3390/e23020184
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Performance in the UK: The Role of Information Entropy in a Novel Slack-Based Data Envelopment Analysis

Abstract: Previous hotel performance studies neglected the role of information entropy in feedback processes between input and output management. This paper focuses on this gap by exploring the relationship between hotel performance at the industry level and the capability of learning by doing and adopting best practices using a sample of 153 UK hotels over a 10-year period between 2008–2017. Besides, this research also fills a literature gap by addressing the issues of measuring hotel performance in light of negative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(99 reference statements)
0
3
0
Order By: Relevance
“…Liquidity was also related to best practices on performance in the hotel industry (Tan et al 2021). Results of this study showed that market dynamics explain the cash flow generation potential and liquidity.…”
Section: Net Profit Margin Net Income Total Salesmentioning
confidence: 73%
“…Liquidity was also related to best practices on performance in the hotel industry (Tan et al 2021). Results of this study showed that market dynamics explain the cash flow generation potential and liquidity.…”
Section: Net Profit Margin Net Income Total Salesmentioning
confidence: 73%
“…Also, Tan et al (2021) considered hotel performance. They investigated the role of information entropy in feedback processes between input and output management as well as evaluated the level of super efficiency with negative values and liquidity variables.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the current developments in FDI, MCDM is a growing field of study, and various approaches are continually being developed and combined to provide a fundamental basis for weighting criteria for ranking alternatives with underlying epistemic uncertainty and measuring performance (Tan et al, 2021;Wanke et al, 2023a). Therefore, this paper fills in the literature gaps by proposing a Robust Compromise (RoCo) MCDM model based on non-linear programming and building upon the findings derived from various other appraoches with regard to alternative rankings and criteria weighting.…”
mentioning
confidence: 99%